Citizen engagement through city apps: Technology adoption approach - Pape, Rita de Orey Botelho Simões Roque de (2020)
Metropolitan areas are constantly evolving, and the smart city concept is gaining traction throughout local governance. The new paradigm for cities lands on an organic, efficient and interconnected structure, where the citizen is placed at the centre. Information and communication technologies (ICT) are the main technological enablers for this change and for citizen engagement, city services and applications (Apps) as one of the channels possible to use. The main objective of the present study is to find the key determinants that enable the adoption of city mobile apps. A theoretical model was created, and an online survey conducted to gather insights of the citizens' perspectives regarding the city apps. The results indicate the model is valid and that perceived usefulness and perceived ease of use are important components to the adoption of city apps. In addition, it was possible to identify some organizational and individual impacts recurring from the use of these apps. This study contributes to a new model of city apps adoption and provides evidence to organisms involved on the implementation and development of these apps.